Buccal versus buccal palatal infiltration for pulpal anesthesia using 2% lidocaine and 4% articaine: A randomized controlled trial - Umesh Kumar; Nikita Garg; Ruchi Vashisht; Amrita Kumari; Charan Kamal Kaur; Akhil Rajput (Journal of Oral Biology and Craniofacial Research)
Background: The inability in achieving complete pulpal anesthesia with standard buccal infiltration especially in cases with SIP used for maxillary teeth. The study aimed to compare the anesthetic efficacy of buccal and buccal plus palatal infiltration technique using 2% lidocaine and 4% articaine in permanent maxillary first molars with the diagnosis of symptomatic irreversible pulpitis (SIP). Material and method: One hundred and twenty-three patients with clinical diagnosis of SIP, aged 18–50 years were randomly allocated to three treatment groups (N = 41). Group 1(BIL): Buccal infiltration technique using 2% lidocaine with 1:80,000 adrenaline. Group 2(BPIL): combination of buccal plus palatal infiltration using 2% Lidocaine with 1:80,000 adrenaline. Group 3(BIA): Buccal infiltration using 4% articaine with 1:100,000 adrenaline. Pain intensity of patients were recorded before and after the administration of local anesthesia during endodontic procedure that is during caries removal, access preparation and pulp removal using Heft-Parker Visual Analog Scale (HP-VAS). Success was defined by “no pain (0 mm)” or “mild pain (0–54 mm)” during endodontic procedure. The anesthetic efficacy rates were analyzed using chi-square tests, age differences using one-way ANOVA. Results: The final analysis included total of 117 patients. Higher success was observed in group II (85%) in comparison to group I (69%) and group III (74%), but the difference was statistically nonsignificant (p > 0.05). Our results demonstrated a nonsignificant difference between genders in all three groups (p > 0.05). Conclusion: The use of buccal plus palatal infiltration and 4% articaine can provide effective anesthesia as standard buccal infiltration and 2% lidocaine for patients with SIP in maxillary first molars.